Segmentasi Pelanggan pada Bisnis Wedding Organizer - Melati, Ina (Binus Business Review, 2010)
Wedding is one of the most important and beautiful thing in a human life, they want that happen only once in their lifetime, thatâs why they arenât mind if they have to spend lot of money to have an unforgettable wedding. For some of Indonesian, wedding party is often considered as someone social status acknowledgement. Wedding party is the one of High Involvement service, that is when a consumer have spent a huge of money and they want the best service as a return. Through Ethnography, segmentation for a Wedding Organizerâs consumer will be described very well and clearly, so that the best service will be delivered to the correct consumer.Â